Rural entrepreneurship and Innovation: some successful women's initiatives - Pato, Lúcia (2017)
Although rural entrepreneurship is an emergent field of study and has emerged as one of the most noticeable ways to promote rural development, the few studies concerning the theme are still incipient. Moreover, a lot of studies focus on rural entrepreneurs as a whole and little research emphasises women’s entrepreneurship, particularly in Portugal. This study explores entrepreneurial initiatives conducted by women in one of the most peripheral areas of Portugal - Montemuro (municipality of Castro Daire), where subsistence agriculture continues to be the main economic activity. These women have been stimulated to develop entrepreneurial activities in their communities, taking advantage of endogenous materials, local culture and traditional knowledge. They try to not only create their own work, but also keep the culture and local traditions alive, therefore contributing to rural development.